Diversidad de aves frugívoras en distintos estados de degradación de los bosques tropicales estacionalmente secos del cantón Zapotillo - Ramírez Ordoñez, Ana Gabriela (2024)
Since it is a very important and threatened ecosystem in terms of biodiversity, Zapotillo's seasonally dry tropical forests (BTES) are an Endemic Bird Area because of its high degree of endemism; Nevertheless, selective logging and overgrazing have resulted in forest degradation, altering the diversity of fruit-eating birds, which play an important role in the restoration of ecosystems as seed dispersers. It was determined through a literature review that 54 count points were sampled at three different locations (La Manga, Cochas, and Corralitos) of the Zapotillo canton in order to assess the richness and abundance of fruit-eating birds in five stages of degradation of the BTES. A total of 630 individuals of 63 bird species were recorded, with the highest abundance and richness occurring in the semi-natural state with 176 and 42, respectively. The 63 species were classified into 35 frugivorous guilds, where 72 individuals and 71 species of frugivorous guilds were identified, respectively; each with 21 species. There are no significant differences between communities of frugivorous birds in the different stages of degradation of the BTES; however, the greatest diversity is found in the intermediate stages of degradation, which responds to the hypothesis of intermediate disturbance, due to the supply of resources and less competition. Furthermore, these factors determine the similarity between bird communities, since in degraded stages, opportunistic species would take advantage of existing resources in order to compete with species that are resistant to disturbances.